How to Stepping up Characters Recognition using CNN Algorithm? - Al-Sadi Khaled; Putra Wanda (University of Respati Yogyakarta, Indonesia, 2022)
Character recognition is very important to understand ancient culture. Various papers proposed numerous to deal with handwritten character recognition. However, several traditional remain drawbacks because methods still rely on operations based on visual capabilities. Therefore, to deal with the issue, we propose a novel recognition model using a Convolutional Neural Network to produce an effective result. To build the model, we collect datasets, do preprocessing, training with several different parameters to get the highest accuracy results. Based on experiments, our proposed model can produce an accuracy quality with a value of 98.00%.